Self-assembly chitosan/gelatin composite coating on icariin-modified TiO2 nanotubes for the regulation of osteoblast bioactivity. (15th February 2016) - Zhang, Yanli; Chen, Liangjiao; Liu, Chundong; Feng, Xiaoli; Wei, Limin; Shao, Longquan
Abstract: The purpose of this study was to fabricate a composite structure consisting of icariin-loaded and chitosan/gelatin-sealed TiO2 nanotubes to control the drug release profile and improve the biocompatibility of the Ti substrates. Icariin was loaded onto TiO2 nanotubes and then sealed with chitosan/gelatin multilayer coatings. The characterization of each specimens were monitored by Field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM), contact angle measurements (CA), X-ray photoelectron spectroscopy (XPS) and High-pressure liquid chromatography (HPLC), respectively. Additionally, the activities of osteoblasts, such as cytoskeletal and proliferative activities, and the cells' osteogenesis-related gene and protein expression on the substrates were investigated in detail. The XPS, AFM and CA results demonstrated that the composite structure of the icariin-loaded and multilayer film-sealed TiO2 nanotubes was successfully fabricated. The prepared specimens stimulated osteoblasts spreading. Furthermore, it exhibited excellent properties, promoting osteoblastic proliferation and up-regulating the expression of bone-related genes, such as osteopontin, type I collagen and osteoprotegerin, while down-regulating RANKL mRNA expression. An icariin-loaded and chitosan/gelatin multilayer-sealed TiO2 nanotube structure can modulate the bioactivity of primary osteoblasts, indicating a potential application on Ti implants to improve biocompatibility and osseointegration. Graphical abstract: Highlights: TiO2 nanotubes were fabricated on the Ti substrate and filled with icariin. Chitosan/gelatin multilayer coating was prepared on the surface of TiO2 substrates. Chitosan/gelatin multilayer coating was prepared on the surface of TiO2 substrates. The multilayer coating decreased adverse effect of TiO2 nanotubes on osteoblasts. The controlled-release of icariin and the coating improve the bioactivity of cells.